2013
DOI: 10.1038/ejcn.2012.159
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance validation studies: alternative approaches to their interpretation

Abstract: Alternative ways of comparing analytical methods that are in use in other branches of biomedical research may prove useful when evaluating the utility of impedance-based methods and other methods for the assessment of body composition in cross-validation studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…Validation studies in clinical populations have typically reported good mean‐level agreement between bioimpedance and reference methods based on correlation and paired t ‐test statistics, but poor accuracy at the individual level (ie, wide limits of agreement by Bland‐Altman analysis) raises doubts about the capacity of bioimpedance techniques to accurately quantify whole body compartments. Each reference method has a certain amount of inherent error, and it can be argued that the aforementioned statistical techniques used to prove validity do not effectively take into account the errors associated with the reference 20 . Furthermore, prediction equations are scaled to a particular reference method and can produce error when evaluated against a different reference method.…”
mentioning
confidence: 99%
“…Validation studies in clinical populations have typically reported good mean‐level agreement between bioimpedance and reference methods based on correlation and paired t ‐test statistics, but poor accuracy at the individual level (ie, wide limits of agreement by Bland‐Altman analysis) raises doubts about the capacity of bioimpedance techniques to accurately quantify whole body compartments. Each reference method has a certain amount of inherent error, and it can be argued that the aforementioned statistical techniques used to prove validity do not effectively take into account the errors associated with the reference 20 . Furthermore, prediction equations are scaled to a particular reference method and can produce error when evaluated against a different reference method.…”
mentioning
confidence: 99%
“…Limitations associated with the bia technique for predicting body composition in patients with cancer include the assumption of constant hydration and ffm composition, which can be different in obesity, various diseases, various age groups, and various ethnic groups 21,22 . In our opinion, further research with a larger sample size could potentially support our results, providing an avenue for early nutrition intervention and corrective nutritive replacement, which, combined with oncology intervention, might ultimately lead to increased survival in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The Bland‐Altman method has recently been criticized, and suggestions have been made on how to optimize its application and interpretation 74 . ‐ 77 Ludbrook 74 proposed that after plotting the differences against the averages, the next step is to evaluate if the differences are correlated with the averages and, if the P value is not statistically significant for r , then proceed with calculating the standard 95% limits of agreement.…”
Section: Validation Of Bedside Techniques To Assess Lean Tissue In CLmentioning
confidence: 99%
“…They described the repeatability coefficient as the “difference that will be exceeded by only 5% of pairs of measurements on the same subject.” 57 This would allow for evaluating not only the limits of agreement between the 2 methods but also the repeatability (ie, precision) for each method separately. Repeated measures are not always obtained in studies; Ward 75 recently provided a thought‐provoking illustration of how a modified version of that approach might be used when repeated measures are not available to better define the validity of a method, building from a method described for techniques to measure cardiac output 76 , 77 . These authors advocated for the calculation of the percentage error (PE) of the limits of agreement compared with the mean of the measurements as a way of defining a cutoff for acceptability of a method.…”
Section: Validation Of Bedside Techniques To Assess Lean Tissue In CLmentioning
confidence: 99%
See 1 more Smart Citation